Analisa Laporan Keuangan Pertumbuhan Penjualan Bersih pada Tahun 2018 di PT Inti Agri Resources Tbk dan Entitas Anak - Cindy Chandra; Zahra, Annisa; RA, Halisya (CV. Kalimasada Group, 2023)
This research was conducted with the aim of looking at the analysis of financial reports for net sales growth in 2018 which has decreased due to reduced demand for arowana fish for export and poor river water quality in fish breeding at PT. Inti Agri Resources Tbk and Subsidiaries. The data taken from the research is sourced from the Annual Report of PT. Inti Agri Resource Tbk and Subsidiaries in 2018. This research method uses a Quantitative Descriptive method. The results of thestudy show that in 2018 net sales decreased by Rp. 79,728,867,002 from the previous year. This is caused by a decrease in the quality of river water in the arowana fish breeding at PT. Inti Agri Resources Tbk and Subsidiaries